(3WHbGJ GdTGaYjI GdhSWis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3ecI GdeTQaI s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeg hHcGaF eRjOg s
(3BNQgG (B:s
(3hCSCdc GdQGMI ai GdOQjf , hai GdOjf hGdOfjG , hEdi gfG GfJgi gPG GdeNJUQ , faY Gddg Hg hLYdg NGdUkG dhLgg GdcQje s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG JYdjbGJ LjOIs
(3hLGA ai BNQ GdLRA GdChd Cf GdeUfa aQZ efg SfI (B754s
(3hGdChQGb GdChdi hGdCNjQI HNW eZGjQ s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs